2014
DOI: 10.1111/add.12604
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol industry sponsorship and hazardous drinking in UK university students who play sport

Abstract: Aim: To examine whether receipt of alcohol industry sponsorship is associated with problematic drinking in UK university students who play sport.Methods: University students (n=2450) participating in sports were invited to complete a pen-andpaper questionnaire by research staff approaching them at sporting facilities and in university settings. Respondents were asked whether they personally, their team, and/or their club were currently in receipt of sponsorship (e.g., money, free or subsidised travel, or sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 29 publications
4
35
0
Order By: Relevance
“…Two of the studies reported findings from participants under the age of 18 and were conducted in a school-based setting (Davies, 2009; De Bruijn et al , 2012). Three studies recruited participants from university sports settings (O'Brien et al , 2011, 2014; Kelly et al , 2014), and two from community sports clubs and training grounds (O'Brien and Kypri, 2008; Kingsland et al , 2013). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the studies reported findings from participants under the age of 18 and were conducted in a school-based setting (Davies, 2009; De Bruijn et al , 2012). Three studies recruited participants from university sports settings (O'Brien et al , 2011, 2014; Kelly et al , 2014), and two from community sports clubs and training grounds (O'Brien and Kypri, 2008; Kingsland et al , 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Of the studies using adult participants, three measured alcohol consumption using the Alcohol Use Disorders Identification Test (AUDIT), a screening tool devised by the World Health Organisation to detect early signs of hazardous and harmful drinking and identify mild dependence (O'Brien and Kypri, 2008; O'Brien et al , 2011, 2014). AUDIT scores of >8 are defined as indicating hazardous drinking (Babor et al , 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations